Perceived stress, disturbed sleep, and cognitive impairments in patients with work-related stress complaints: a longitudinal study. (4th July 2017) - Eskildsen, Anita; Fentz, Hanne Nørr; Andersen, Lars Peter; Pedersen, Anders Degn; Kristensen, Simon Bang; Andersen, Johan Hviid
Abstract: Patients on sick leave due to work-related stress often present with cognitive impairments as well as sleep disturbances. The aim of this longitudinal study was to examine the role of perceived stress and sleep disturbances in the longitudinal development in cognitive impairments in a group of patients with prolonged work-related stress ( N  = 60) during a period of 12 months following initial professional care-seeking. Objective cognitive impairments (neuropsychological tests) were measured on two occasions – at initial professional care-seeking and at 12-month follow-up. Questionnaires on perceived stress, sleep disturbances, and cognitive complaints were completed seven times during the 12 months which facilitated multilevel analysis with segregation of within-person (change) and between-person (baseline level) components of the time-varying predictors (perceived stress and sleep disturbances). Change in perceived stress was associated with concurrent and subsequent change in self-reported cognitive complaints over the period of 12 months and to a lesser extent the change in performance on neuropsychological tests of processing speed from baseline to 12-month follow-up. Change in sleep disturbances was also associated with concurrent and subsequent change in self-reported cognitive complaints over the 12 months but not with change on neuropsychological test performance. Although the mechanism behind the improvement in cognitive impairments in patients with work-related stress should be further explored in future studies, the results could suggest that improvement in cognitive impairments is partly mediated by decreasing levels of perceived stress and, to a lesser extent, decreasing levels of sleep disturbances. Lay summary This study examines the role of perceived stress and sleep disturbances in respect to the development of cognitive impairments (e.g. memory and concentration) in a group of patients with work-related stress. We found that change in cognitive impairments seems to be partly explained by change in perceived stress and, to a lesser extent, sleep disturbances over time. This could suggest that cognitive impairments can be reduced by stress management interventions which aim to reduce perceived stress and sleep disturbances but future studies are needed to confirm this interpretation.